The Analysis of Factors, Types, and Strategies for Handling Complaints by Front Office Employees of Hotel Sibayak International Berastagi - Thomas Maranatha Tambun; Risnashari (International Journal of Travel, Hospitality and Events, 2026)
Guest complaints regarding hotel front office operations remain a significant issue that affects service quality and guest satisfaction. However, previous studies have tended to focus solely on the descriptive identification of complaint types without providing an empirical explanation of the relationship between complaint handling strategies and improvements in service quality and guest satisfaction. This study aims to analyze the factors, types, and complaint handling strategies implemented by front office staff at Hotel Sibayak Internasional Berastagi, while also explaining how structured handling procedures contribute to improved service outcomes. This study employs a descriptive qualitative approach based on the author’s observations and work experience in the Front Office Department. The results of the study indicate that guest complaints stem from internal factors (service performance, professionalism, and communication) as well as external factors (facilities, room readiness, and operational constraints). There are five main categories of complaints: reservations, service, facilities, billing, and security. Key analytical findings indicate that the implementation of the ILEAD mechanism—Identify, Listen, Empathize, Apologize, and Deliver Solution—serves as a structured service recovery process to reduce guest dissatisfaction and support service consistency in accordance with operational standards. Theoretically, this study contributes to the hospitality service literature by demonstrating the role of structured complaint handling as a mechanism linking operational performance to guest satisfaction. Practically, the research findings provide managerial implications for hotel management to strengthen front-office training, standardize complaint-handling procedures, and improve service responsiveness to enhance guest satisfaction and the hotel’s reputation.